2020
DOI: 10.3390/jfb11040083
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Interactions with Dental and Medical Materials

Abstract: Fundamental scientific understanding of oral diseases associated with tissue-contacting dental and medical devices is primordial to facilitate pathways for their translation to clinical use [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In general, macroroughness is described to improve bone–implant interactions, but it is well known that the optimal surface roughness should be about 1 µm to promote the osteogenic differentiation of MSCs [ 39 , 40 ]. Unfortunately, increasing surface roughness can promote the microbial colonization of the implant surface, as initial bacterial adhesion begins at sites that offer shelter [ 41 , 42 ]. Several studies have shown that, in order to reduce bacterial adhesion, a nanoscale surface with a roughness of <200 nm is the most effective, since the depth and period of the nanostructures are smaller than most bacteria [ 12 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, macroroughness is described to improve bone–implant interactions, but it is well known that the optimal surface roughness should be about 1 µm to promote the osteogenic differentiation of MSCs [ 39 , 40 ]. Unfortunately, increasing surface roughness can promote the microbial colonization of the implant surface, as initial bacterial adhesion begins at sites that offer shelter [ 41 , 42 ]. Several studies have shown that, in order to reduce bacterial adhesion, a nanoscale surface with a roughness of <200 nm is the most effective, since the depth and period of the nanostructures are smaller than most bacteria [ 12 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The last decade brought significant improvements of mechanical material properties as well as surface characteristics and biocompatibility of composites used in dentistry [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Focus on new bioactive compounds in composites to prevent dental caries development and progression has led researchers to the use of nanotechnologies [ 9 , 10 ]. Composite configuration has significant impact not only on 3D-printed appliance properties [ 11 , 12 , 13 ] but also on adhesion efficacy when used as adhesive for an appliance [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research led to significant improvements of mechanical strength, surface characteristics and biocompatibility of composites used in dentistry [1 -8]. Focus on new bioactive compounds in composites to prevent dental caries development and progression has led researchers to use of nanotechnologies [9,10]. Composite configuration has significant impact not only on 3D-printed appliance properties [11 -13] but also on adhesion efficacy when used as adhesive for an appliance [14,15].…”
Section: Introductionmentioning
confidence: 99%